BIM : contractual and legal perspectives - Barnes, Peter, active 2025 (Emerald Publishing Limited, 2025)
BIM: Contractual and Legal Perspectives is a guide to the legal and contractual issues that need to be considered when operating under Building Information Modelling (BIM). The book illustrates the ways in which these issues are presently addressed and considers emerging approaches that can support the effective integration of BIM within project delivery. Coverage includes: BIM documentation and key roles and responsibilities; incorporation of BIM within standard form contracts, including NEC and JCT new contracts; smart contracts and blockchain; Intellectual Property Rights and copyright; design liability and professional indemnity; information security; dispute resolution, including use of models and artificial intelligence. BIM: Contractual and Legal Perspectives is an essential reference for a range of built environment professionals, including civil engineers and architects, and also professionals in commercial and management roles including project managers; quantity surveyors, client-side practitioners, legal professionals and digital specialists.